Blockade of LIRs as a new approach for diagnostics and treatment of ATLL malignancy - M. Keikha; M. Karbalaei (Инфекция и иммунитет, 2022)
In the new world of medicine, one of the main concerns in the field of infectious diseases has been focused on Human T-cell Leukemia Virus type 1 (HTLV-1). During the infection, lymphocyte inhibitory receptors (LIRs) play a prominent role in the occurrence of adult T-cell leukemia/lymphoma (ATLL). These receptors include LAG3, PD-1, TIGIT, CD160, TIM3, and 2B4. First, we have collected all microarray information on the profile of HTLV-1 infected patients from the Gene Expression Omnibus (http://www.ncbi.nlm.gov/geo) database until March 2020, in order to identify the microarray related to evolutionary development of LTRs during various phases of HTLV-1 infection in human peripheral blood CD4+ T cells by searching for keywords such as “Human T-lymphotropic virus type I (HTLV-1)”, “Homo sapiens”, “ATLL”, and “Whole genome sequencing”. Considering the main goal of the study, we have only assessed data related to Homo sapiens particularly CD4+ T cell lineage from human subjects infected with HTLV-1. We evaluated these receptors in ATLL patients compared to healthy control (HC) individuals and HTLV-1 infected-asymptomatic carriers (ASCs). Out of all 18 identified records, we only selected and analyzed three studies: GSE19080, GSE33615, and GSE57259, which satisfied inclusion criteria with proper quality analysis of ATLL vs. normal, ATLL vs. asymptomatic carrier as well as asymptomatic carrier vs. normal. Unfortunately, we could not analyze various stages of ATLL malignancy (acute, lymphomatous, chronic and smoldering) in all included studies due to the lack of sufficient information. Finally, based on Benjamini–Hochberg False discovery rate (FDR), the differentially expressed genes (DEGs) were selected for several categories. Hence, for the first time we demonstrated that the expression rate of LIRs in ATLL group was higher than either in asymptomatic carrier or healthy donor groups. As a conclusion, it seems that the blockade of LIRs has a pivotal role in diagnostics and treatment of ATLL malignancy.